PRELIMINARY HISTOANATOMICAL STUDY OF SAPRIA HIMALAYANA GRIFF. F. ALBOVINOSA FLOWER BUDS AND ITS INTERSECTION WITH ITS HOST PLANT TETRASTIGMA LAOTICUM GAGNEP. - Adhityo WICAKSONO; Hữu Đăng TRẦN; Syarifah Haniera Sheikh KAMAL (Journal of Plant Development, 2021)
Sapria, a holoparasitic plant of Rafflesiaceae is still understudied in term of anatomical, even more in histoanatomical study. This study aimed to perform preliminary observation on Sapria himalayana Griff. f. albovinosa morphology on its early and late stage of flower bud development inside its host, Tetrastigma laoticum Gagnep. (Vitaceae). The results show the progression from the early flower bud as it starts to grow in the host vascular cambium area towards proximal direction to reach the host xylem and distal direction to reach the host phloem and to reach the next stage of the life cycle, into the late flower bud where differentiation occurs. In late flower bud, some primordial of the organs are visible as the flower bud grows larger distally towards the periderm. This development pattern is similar to the progression of development in the previous studies in Rafflesia and Rhizanthes, where endophytic growth was observable in both proximal (xylem area) and distal (peridermal). Future comparative study is encouraged, especially to compare between Sapria species and between different stages of growth. Although, an efficient method and less invasive way of sampling is encouraged to prevent decline of Sapria species in the wild.